2020
DOI: 10.1017/pasa.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Self-similar structure of resistive ADAFs with outflow and large-scale magnetic field

Abstract: The observations and simulations have revealed that large-scale magnetic field and outflows can exist in the inner regions of an advection-dominated accretion disc where the resistive diffusion may also be important. In the present paper, the roles of large-scale magnetic field and outflows in the structure of resistive advection-dominated accretion discs are explored by assuming that the accretion flow is radially self-similar. In the non-ideal magnetohydrodynamic (MHD) approximation, the results show that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 100 publications
1
4
0
Order By: Relevance
“…( 19)). These results are in excellent agreement with previous work (e.g., Zhang and Dai 2008;Ghoreyshi and Shadmehri 2020;Ghoreyshi 2020). Now, we explore the effects of s on the physical variables of hot accretion flows when η 0 = 0.1.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…( 19)). These results are in excellent agreement with previous work (e.g., Zhang and Dai 2008;Ghoreyshi and Shadmehri 2020;Ghoreyshi 2020). Now, we explore the effects of s on the physical variables of hot accretion flows when η 0 = 0.1.…”
Section: Resultssupporting
confidence: 91%
“…Previous work showed that in the ideal MHD the vertical component of the magnetic field reduces the velocities discussed in this paper (e.g., Mosallanezhad et al 2013). However, the effect of the vertical field component on the resistive disks structure depends on the magnetic diffusivity (Ghoreyshi 2020). Then accounting for this component may yield different results.…”
Section: Summary and Discussionmentioning
confidence: 77%
See 3 more Smart Citations